Influence of nanosilica/polyurethane composite coating on IR effectiveness and visible light transmission properties of polyethylene - Chee, Ching Yern; Yaacob, Iskandar Idris (Trans Tech Publications, Switzerland, 2010)
Polyethylene (PE) film was coated with nanosilica-polyurethane layer using rod Mayer process. The nanosilica-polyurethane system was prepared by dispersing nanosilica (SiO2) powder into solvent borne polyurethane (PU) binder under vigorous stirring. Various compositions of nanosilica-polyurethane slurry were prepared. A battery of characterization procedures were used to study the properties of the nanocomposite coating. ATR FTIR confirmed the presence of functional groups of silica and polyurethane. The uniformity of silica dispersion was probed using scanning electron microscopy (SEM). With the introduction of nanosilica to polyurethane binder, the visible light transmittance and ultra-violet (UV) radiation of nanosilica-polyurethane system reduced with increasing nanosilica content and coating layer thickness. The PE coated with nanocomposite containing 14wt% nanosilica and with 8 μm coating thickness showed >88% transmittance in the visible light region. Infrared (IR) effectiveness (between 7 μm to 13 μm wavelengths) measurements by FTIR also showed that nanosilica/polyurethane system coating on PE film surface greatly improved the infrared opacity properties of PE film. © (2010) Trans Tech Publications.